NOTES ON THE STATUS OF MAMMALIAN FAUNA OF THE LAWACHARA NATIONAL PARK, BANGLADESH - Aziz, Md. Abdul (Ecoprint: An International Journal of Ecology, 2013)
This paper presents a checklist of mammalian species of the Lawachara National Park, Bangladesh with notes on their status and conservation threats. A total of 39 species belonging to seven orders and 21 families were recorded. Of these, Carnivora (38%), Rodentia (24%), Primates (15%), Chiroptera (13%) and Artiodactyla (5%) were major. Thirty six per cent of the recorded mammals were common followed by uncommon (26%), rare (23%) and very common (15%). Nationally, 51% of the recorded species face different categories of threats followed by not threatened (28%) and data deficient (21%). In terms of global status, 23% of the species are threatened and 73% species are under lower risk category. Primates, herbivores and carnivores face severe threats primarily stemming from habitat loss and fragmentation, wildlife poaching and human disturbance. Arresting illegal tree felling and over-exploitation of forest resources, restoration of degraded habitats and regulative tourism activities should urgently be addressed for long-term conservation of mammalian species in the park. DOI: http://dx.doi.org/10.3126/eco.v18i0.9398 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 45-53 Uploaded date: 12/20/2013